A numerical study on the vortex-induced vibration of flexible cylinders covered with differently placed buoyancy modules. (January 2021) - Zheng, Hanxu; Wang, Jiasong
Abstract: Buoyancy modules are essential parts in the offshore oil and gas drilling and production practices. They provide weight compensation for the riser and help avoid excessive top tension exerted by the floating platform. However, the deployment of buoyancy modules with larger diameter than the bare riser may alter the geometric shape of the riser system and greatly influence the hydrodynamic performance. Engineering designs with buoyancy modules are mostly based on experience and rigid cylinder forced vibration experimental data. Since it is difficult if not impossible to perform real sea experiments, numerical simulation becomes important in aiding the buoyancy module design and setup. In the present work, a fluid–structure interaction code based on the computational fluid dynamic model is firstly validated with the riser experimental data from MARINTEK (the Norwegian Marine Technology Research Institute) and then used to simulate the riser responses with different continuous buoyancy module setups. The Reynolds number based on the incoming velocity and the bluff body diameter ranges from 4 × 1 0 3 to 1 . 68 × 1 0 4 . The simulation results suggest that the shape alteration from the buoyancy deployment will change the vortex-induced vibration(VIV) response mode along with the vibration frequency. The cylinder fatigue damage, travelling wave response and the fluid–structure energy transfer characters are discussed under different buoyancy module setups.